Determination of physical and chemical soil parameters on selenium adsorption, desorption by rice growing soil - Alifar, Nafiseh; Abdul Rahman, Zaharah; Ishak, Che Fauziah; Awang, Yahya; Khayambashi, B. (Asian Network for Scientific Information, 2014)
Studies on Selenium adsorption was conducted in laboratory studies for some different rice growing soils of Malaysia at pH 4 and 7. Soils were equilibrated with 0.01 M CaCl2 and Na2SeO3 solution to measure relative adsorption of Selenium as sodium Selenite ions. In general, the adsorption of Se on different soils at both pH, increased with increase in the level of Se added. Adsorption data were fitted well to Langmuir model. Maximum adsorption (Qm) was correlated with organic carbon at both pH 4 (R = 0.77**) and pH 7 (R = 0.76**) and log K (R = 0.71** and R = 00.81**) at pH 4 and 7 respectively and also Qm was correlated with percent of clay (R = 0.59*) and CEC (R = 0.58*) at pH 7. Desorption data showed the higher amount of desorbed Se was achieved at pH 7 than pH 4 in all type of soil except TIP2, KBK, Mb and UPM.